Is the 8th edition of the Union for International Cancer Control staging of oral cancer good enough?. Issue 4 (May 2018) - Vuity, D.; McMahon, J.; Takhiuddin, S.; Slinger, C.; McLellan, D.; Wales, C.; MacIver, C.; Thomson, E.; McCaul, J.; Hislop, S.; Lamb, C.; Stalker, E.; et al.
Abstract: Depth of invasion is an important predictor of survival. A study by the International Consortium (ICOR) for Outcome Research proposed incorporation of it (together with the greatest surface dimension, or the anatomical criteria, or both) into the T stage. This has been adopted in part by the 8th edition of the Union for International Cancer Control (UICC) TNM 8 classification of malignant tumours for oral squamous cell carcinoma (SCC). Our aim was to verify depth of invasion as an independent prognostic factor, and to validate the staging by comparing it with that specified in the 7th edition (TNM 7) and the T-staging model proposed by the International Consortium. We retrospectively studied 449 patients who had had operations for a previously untreated primary oral cancer between 2006 and 2014 at a single centre, and analysed the independent predictive value of depth of invasion for both disease-specific and overall survival. It was an independent predictor of disease-specific survival as were sex, perineural invasion, and N stage. It was also an independent predictor of overall survival together with sex and N status. Staging in TNM 8 gave a better balance of distribution than that in TNM 7, but did not discriminate between prognosis in patients with T3 and T4 disease. The proposed International Consortium rules for T-staging gave an improved balance in distribution and hazard discrimination. The incorporation of depth of invasion into the T-staging rules for oral SCC improved prognostic accuracy and is likely to influence the selection of patients for adjuvant treatment. Our findings suggest that the TNM 8 staging lacks hazard discrimination in patients with locally-advanced disease because its T4 staging is restricted to anatomical criteria.